No relationship between prenatal androgen exposure and autistic traits: convergent evidence from studies of children with congenital adrenal hyperplasia and of amniotic testosterone concentrations in typically developing children. (27th July 2016) - Kung, Karson T. F.; Spencer, Debra; Pasterski, Vickie; Neufeld, Sharon; Glover, Vivette; O'Connor, Thomas G.; Hindmarsh, Peter C.; Hughes, Ieuan A.; Acerini, Carlo L.; Hines, Melissa
Abstract : Background: There is a marked male preponderance in autism spectrum conditions. The extreme male brain theory and the fetal androgen theory of autism suggest that elevated prenatal testosterone exposure is a key contributor to autistic traits. The current paper reports findings from two separate studies that test this hypothesis. Methods: A parent‐report questionnaire, the Childhood Autism Spectrum Test (CAST), was employed to measure autistic traits in both studies. The first study examined autistic traits in young children with congenital adrenal hyperplasia (CAH), a condition causing unusually high concentrations of testosterone prenatally in girls. Eighty one children with CAH (43 girls) and 72 unaffected relatives (41 girls), aged 4–11 years, were assessed. The second study examined autistic traits in relation to amniotic testosterone in 92 typically developing children (48 girls), aged 3–5 years. Results: Findings from neither study supported the association between prenatal androgen (testosterone) exposure and autistic traits. Specifically, young girls with and without CAH did not differ significantly in CAST scores and amniotic testosterone concentrations were not significantly associated with CAST scores in boys, girls, or the whole sample. Conclusions: These studies do not support a relationship between prenatal testosterone exposure and autistic traits. These findings augment prior research suggesting no consistent relationship between early androgen exposure and autistic traits. Abstract : Read the Commentary on this article at doi:10.1111/jcpp.12628